Pre-lithiation negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202610856082.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-12
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]本发明针对现有化学预锂化存在的缺陷,尤其是预锂化负极材料与固态电解质的界面兼容性差,难以适配电极制备工艺的缺陷和不足,提供一种预锂化负极材料的制备方法,解决预锂化材料的高活性与加工环境的矛盾,同时解决了预锂化负极材料与固态电解质的界面兼容性问题
本发明提供了一种预锂化负极材料,在预锂化处理的硅材料表面原位构建稳定的钝化层,抑制高活性硅与硫化物、氧化物等固态电解质的有害副反应,形成稳定、低阻抗的离子/电子传输界面,且通过表面钝化显著提高预锂材料的空气稳定性,拓宽了电极加工窗口,使其能够兼容常规干燥室环境下的极片制备工艺,使化学预锂化技术能够安全应用于对界面极为敏感的固态电池体系。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a pre-lithiated anode material, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries have been widely used due to their high specific energy and long lifespan. However, traditional liquid lithium batteries use flammable organic electrolytes, posing safety hazards and limiting energy density improvements. All-solid-state batteries using solid electrolytes offer higher safety and theoretical energy density, and are considered an important direction for next-generation batteries. Silicon (Si) materials, due to their extremely high theoretical specific capacity (approximately 4200 mAh / g), are highly promising high-energy-density anode materials, but their application in solid-state batteries faces two major challenges. Firstly, there is the significant volume effect: silicon expands dramatically (approximately 300%) during charge and discharge, leading to material pulverization and repeated cracking and regeneration of the solid electrolyte interphase (SEI), continuously consuming limited lithium sources and electrolytes, resulting in rapid capacity decay and low efficiency. Secondly, there is the low initial coulombic efficiency (ICE): the initial formation of the SEI film on the silicon surface irreversibly consumes a large number of lithium ions, with the initial coulombic efficiency typically only 80%–85%, severely reducing the actual energy density of the entire battery.
[0003] To overcome the above problems, pre-lithiation technology is a recognized effective solution. Existing pre-lithiation technologies mainly include electrochemical pre-lithiation, contact lithium foil pre-lithiation, and chemical pre-lithiation. Chemical pre-lithiation has the following main drawbacks: Reagent sensitivity and safety: Commonly used pre-lithiation reagents (such as lithium naphthalene) are extremely sensitive to air and moisture, posing a danger and requiring stringent operation (a strict glove box environment), making industrial production difficult. Compatibility with solid-state electrolytes: Existing chemical pre-lithiation research mainly focuses on liquid batteries and does not fully consider interfacial compatibility with solid-state electrolytes (especially sulfide electrolytes that are sensitive to air / water and have narrow electrochemical windows). Residual organic solvents or byproducts after pre-lithiation may contaminate the solid-state electrolyte, triggering harmful interfacial side reactions. Furthermore, electrode process adaptability and extremely narrow processing window: Pre-lithiated silicon materials (LixSi) exhibit extremely high chemical activity and are extremely sensitive to trace amounts of oxygen and moisture in the environment. In actual dry or wet electrode fabrication processes, spontaneous oxidation failure easily occurs, resulting in an extremely narrow processing window (operation must be carried out entirely in a glove box with extremely low dew points). Meanwhile, highly active exposed Li x The Si surface is highly susceptible to continuous interfacial side reactions with the solid electrolyte inside the battery, leading to a sharp increase in interfacial impedance and battery failure. Summary of the Invention
[0004] This invention addresses the shortcomings of existing chemical prelithiation methods, particularly the poor interfacial compatibility between prelithiated anode materials and solid electrolytes, and the difficulty in adapting them to electrode fabrication processes. It provides a method for preparing prelithiated anode materials, resolving the contradiction between the high activity of prelithiated materials and the processing environment, while also solving the interfacial compatibility problem between prelithiated anode materials and solid electrolytes.
[0005] Another objective of this invention is to provide a method for preparing a pre-lithiated anode material.
[0006] Another object of the present invention is to provide a negative electrode sheet.
[0007] Another object of the present invention is to provide a battery cell.
[0008] Another object of the present invention is to provide a battery cell module.
[0009] Another object of the present invention is to provide a battery pack.
[0010] Another object of the present invention is to provide an electrical device.
[0011] In a first aspect, the present invention specifically protects a pre-lithiated anode material, which is composed of silicon particles with a core-shell structure, wherein the core is a silicon matrix phase, the shell is a lithium-silicon alloy phase, and the outer layer of the lithium-silicon alloy phase is covered with an oxygen-containing passivation layer. The oxygen-containing passivation layer comprises Li2O, Li2CO3, and SiO2. x The composite phase has an oxygen-containing passivation layer with a thickness of 1 nm to 1 μm and a specific surface area of 0.1 to 200 m². 2 / g.
[0012] According to the pre-lithiation anode material protected by the present invention, preferably, the thickness of the oxygen-containing passivation layer is 5~30nm, more preferably 5~25nm.
[0013] According to the pre-lithiation anode material protected by the present invention, preferably, the specific surface area of the oxygen-containing passivation layer is 2~20m². 2 / g.
[0014] According to the pre-lithiation anode material protected by the present invention, preferably, the lithium-silicon alloy phase is Li. x The values of Si and x are 1.5 to 3.5, preferably 2 to 3.2.
[0015] Secondly, this invention also specifically protects a method for preparing a pre-lithiated anode material, comprising the following steps: S1. The silicon-based anode material powder is immersed in a pre-lithiation solution to carry out a pre-lithiation reaction at a reaction temperature of 20~60℃ and a reaction time of 0.5~4h to obtain a pre-lithiation silicon-based anode material; S2. The pre-lithiated silicon-based anode material is placed in an atmosphere with an oxygen volume concentration of 0.1-5% for surface passivation treatment to obtain the pre-lithiated silicon-based anode material. The treatment time is 10-20 min.
[0016] According to the preparation method of the pre-lithiated anode material protected by the present invention, preferably, the pre-lithiated solution is an ether solution of 1~2 mol / L lithium complex.
[0017] According to the preparation method of the pre-lithiated anode material protected by the present invention, preferably, the lithium complex is selected from one or more of biphenyl lithium complex and naphthol lithium complex, more preferably, the naphthol lithium complex is selected from one or more of 1-methylnaphthalene lithium complex, 2-methylnaphthalene lithium complex, 1,2-dimethylnaphthalene lithium complex, 3,3-dimethylnaphthalene lithium complex, 4,4-dimethylnaphthalene lithium complex and 3,3-4,4-tetramethylnaphthalene lithium complex.
[0018] According to the preparation method of the pre-lithiated anode material protected by the present invention, preferably, the solvent of the ether solution is selected from at least one of dioxolane, tetrahydrofuran, ethylene glycol dimethyl ether and 2-methyltetrahydrofuran.
[0019] According to the method for preparing the pre-lithiated anode material protected by the present invention, preferably, the pre-lithiation solution is prepared by the following method: Under an inert atmosphere, a lithium source and an aromatic hydrocarbon ligand are reacted in an ether solvent to obtain a pre-lithiation solution of a lithium complex. The lithium source concentration is 0.5~2.0 mol / L, and the molar ratio of lithium source to aromatic hydrocarbon ligand is 1:0.1~10.
[0020] The method for preparing the pre-lithiated anode material protected by the present invention preferably further includes the following steps: S3. Perform reverse testing on the pre-lithiation silicon-based anode material of S2, and adjust the pre-lithiation processing parameters of S1 based on the reverse testing results to form a closed-loop control of the pre-lithiation degree. Preferably, the reverse detection includes reverse detection of alloy phase composition and actual compensation lithium content; Preferably, the detection method for the reverse detection is selected from any one of acid-base titration, XPS (X-ray Photoelectron Spectroscopy) depth analysis, or half-cell testing.
[0021] Thirdly, the present invention also specifically protects a negative electrode sheet, comprising a current collector and an electrode material layer on the surface of the current collector, characterized in that the electrode material layer uses the pre-lithiated negative electrode material as the active material.
[0022] According to the negative electrode sheet protected by the present invention, preferably, the method for preparing the negative electrode sheet is as follows: The pre-lithiated anode material, solid electrolyte powder, conductive agent and binder are mixed, and the anode sheet is obtained by dry electrode process or wet electrode process. Preferably, the solid electrolyte powder is selected from one or more of oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, nitride solid electrolytes, and hydride solid electrolytes; The preferred mass ratio of the pre-lithiated anode material, solid electrolyte powder, conductive agent and binder is 50~90:20~40:5~10:3~8.
[0023] Fourthly, the present invention also specifically protects a battery cell, including the negative electrode sheet.
[0024] Fifthly, the present invention also specifically protects a battery cell module, including the negative electrode sheet or the battery cell.
[0025] Sixthly, the present invention also specifically protects a battery pack, including the negative electrode sheet, the battery cell, or the battery cell module.
[0026] In a seventh aspect, the present invention also specifically protects an electrical device, including the negative electrode sheet, the battery cell, the battery cell module, or the battery pack.
[0027] According to the electrical appliance protected by the present invention, preferably, the electrical appliance includes a vehicle.
[0028] Beneficial effects: This invention provides a pre-lithiated anode material that constructs a stable passivation layer in situ on the surface of pre-lithiated silicon material, suppressing harmful side reactions between highly active silicon and solid electrolytes such as sulfides and oxides, forming a stable, low-impedance ion / electron transport interface, and significantly improving the air stability of the pre-lithiated material through surface passivation, thus broadening the electrode processing window and enabling it to be compatible with electrode preparation processes under conventional dry chamber environments. This allows chemical pre-lithiation technology to be safely applied to solid-state battery systems that are extremely sensitive to interfaces.
[0029] The pre-lithiation anode material preparation method provided by this invention not only achieves precise control of the pre-lithiation degree of the pre-lithiation anode material through specific pre-lithiation treatment and surface passivation process, but also effectively improves the interface performance of the pre-lithiation anode material. When applied to silicon-based all-solid-state batteries, it exhibits excellent performance in terms of first-efficiency, cycle stability and resistance to air aging. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0031] In a specific embodiment, the present invention provides a pre-lithiated anode material, which is composed of silicon particles with a core-shell structure, wherein the core is a silicon matrix phase, the shell is a lithium-silicon alloy phase, and the outer layer of the lithium-silicon alloy phase is covered with an oxygen-containing passivation layer. The oxygen-containing passivation layer comprises Li2O, Li2CO3, and SiO2. x The composite phase has an oxygen-containing passivation layer with a thickness of 1 nm to 1 μm and a specific surface area of 0.1 to 200 m². 2 / g.
[0032] Pre-lithiation involves introducing active lithium into the negative electrode material before the battery is fully cycled to compensate for irreversible lithium loss during the first charge-discharge process. Compared to the shortcomings of conventional pre-lithiation treatment of negative electrode materials, the pre-lithiated negative electrode material provided by this invention has an oxygen-containing passivation layer covering the outer layer of the lithium-silicon alloy phase formed during pre-lithiation. This solves the interfacial compatibility problem between the highly active silicon material after pre-lithiation and solid electrolytes such as sulfides, oxides, and halides, effectively suppressing harmful interfacial side reactions and forming a stable, low-impedance ion / electron transport interface. Furthermore, the extremely thin and dense oxygen-containing passivation layer covering the silicon alloy phase of the pre-lithiated negative electrode material also solves its sensitivity to trace amounts of oxygen and moisture in the environment, significantly improving the air stability of the pre-lithiated material, widening the electrode processing window, and enabling it to be compatible with electrode fabrication processes under conventional dry chamber environments. It can be safely and stably integrated into dry or wet electrode fabrication processes for solid-state batteries while maintaining long-term interfacial stability.
[0033] The oxygen-containing passivation layer of this invention has a thickness of 1 nm to 1 μm. This extremely thin passivation layer is beneficial for reducing interfacial impedance, increasing the proportion of active material, and ensuring rapid lithium-ion transport. Simultaneously, the specific surface area of the oxygen-containing passivation layer is controlled to be 0.1 to 200 μm². 2 / g has a dense surface protective structure that can effectively block side reaction channels, prevent solid electrolytes and trace impurities from directly contacting the highly active lithium-silicon alloy, suppress interfacial side reactions, and improve interfacial mechanical stability. The dense layer can withstand the stress caused by silicon volume changes, is not easy to break or fall off, maintains long-term interfacial stability, suppresses active lithium loss, and improves cycle stability.
[0034] In some specific embodiments, the thickness of the oxygen-containing passivation layer formed by the present invention can be, for example, a point value or any range of values such as 1nm, 5nm, 10nm, 15nm, 25nm, 30nm, 50nm, 80nm, 100nm, 200nm, 500nm, 800nm, 1um, preferably 5~30nm, more preferably 5~25nm.
[0035] The specific surface area of the oxygen-containing passivation layer formed by the present invention can be, for example, 0.1 m². 2 / g, 0.5m 2 / g, 1m 2 / g、2m 2 / g, 10m 2 / g、20m 2 / g, 50m 2 / g, 100m 2 / g, 150m 2 / g、180m 2 / g、200m 2 / g is a point value or any range of values, preferably 2~20m. 2 / g.
[0036] In some specific embodiments, the oxygen-containing passivation layer mentioned in this invention has a thickness of 5 nm and a specific surface area of 20 m². 2 / g.
[0037] In some specific embodiments, the oxygen-containing passivation layer mentioned in this invention has a thickness of 15 nm and a specific surface area of 20 m². 2 / g.
[0038] In some specific embodiments, the oxygen-containing passivation layer mentioned in this invention has a thickness of 30 nm and a specific surface area of 20 m². 2 / g.
[0039] In some specific embodiments, the oxygen-containing passivation layer mentioned in this invention has a thickness of 25 nm and a specific surface area of 2 m². 2 / g.
[0040] In some specific embodiments, the oxygen-containing passivation layer mentioned in this invention is generated in situ by the following method: The silicon-based anode material powder with pre-lithiation reaction is placed in an atmosphere with an oxygen volume concentration of 0.1-5% for surface passivation treatment to generate an oxygen-containing passivation layer in situ. The treatment time is 10-20 minutes.
[0041] In some specific exemplary embodiments, the oxygen volume concentration in the operating atmosphere for preparing the oxygen-containing passivation layer mentioned in this invention can be any point value or range value such as 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., preferably in the range of 1 to 2%. Other gas components in the atmosphere can be inert gases such as argon or stable gases such as nitrogen.
[0042] By controlling the formation process of the oxygen-containing passivation layer, especially the control of oxygen volume concentration and reaction time, an extremely thin and dense oxygen-containing passivation layer can be precisely generated in situ on the surface of lithium-silicon alloy phase particles, thereby improving the interface improvement performance of pre-lithiated silicon-based anode materials.
[0043] In a specific embodiment, the lithium-silicon alloy phase particles mentioned in this invention are Li x Si, x takes values from 1.5 to 3.2.
[0044] In some specific exemplary embodiments, the value of x can be a point value such as 1.5, 1.8, 2.1, 2.5, 2.8, 3.0, 3.2, or any range of values.
[0045] In a specific embodiment, the present invention also provides a method for preparing a pre-lithiated anode material, comprising the following steps: S1. The silicon-based anode material powder is immersed in a pre-lithiation solution to carry out a pre-lithiation reaction at a reaction temperature of 20~60℃ and a reaction time of 0.5~4h to obtain a pre-lithiation silicon-based anode material; S2. The pre-lithiated silicon-based anode material is placed in an atmosphere with an oxygen volume concentration of 0.1-5% for surface passivation treatment to obtain the pre-lithiated silicon-based anode material. The treatment time is 10-20 min.
[0046] This invention provides a relatively mild, safe, and easily controllable chemical pre-lithiation method, reducing the stringent requirements on the production environment. Silicon-based anode material powder is immersed in a pre-lithiation solution and stirred to react. This process allows for a controllable chemical alloying reaction between the lithium complex and silicon, forming a uniform lithium-silicon alloy phase (Li₂) on the surface and near the surface of the silicon particles. x Si).
[0047] In S1, the forward control of the pre-lithiation reaction temperature and time can achieve control over the degree of pre-lithiation (i.e., the amount of lithium embedded in silicon, characterized by the initial lithium-silicon alloy Li). x Precise control of the value of x in Si.
[0048] After the reaction is complete, the material is thoroughly cleaned multiple times with an inert solvent (such as alkanes or aromatics) that is harmless to the subsequent solid electrolyte to completely remove residual active lithium reagents and soluble byproducts. Then, it is dried at low temperature under vacuum or inert atmosphere to obtain pre-lithiated silicon-based anode material.
[0049] The low-oxygen surface passivation treatment in step S2 can be applied to the lithium-silicon alloy phase Li x A uniform, dense, and extremely thin oxygen-containing passivation layer is formed in situ on the surface of Si particles.
[0050] In some specific exemplary embodiments, the silicon-based anode material mentioned in this invention can be independently selected from at least one of micron-sized silicon, nano-sized silicon, silicon-carbon, and silicon-oxygen.
[0051] In some specific embodiments, the pre-lithiation solution mentioned in this invention is an ether solution of a 1-2 mol / L lithium complex.
[0052] In some specific exemplary embodiments, the concentration of the ether solution of the lithium complex mentioned in this invention can be a point value such as 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, or any range of values.
[0053] In some specific exemplary embodiments, the lithium complexes mentioned in this invention may be selected from one or more of lithium biphenyl and lithium naphthene complexes. Specifically, the lithium naphthene complexes may be selected from one or more of 1-methyllithium naphthene complexes, 2-methyllithium naphthene complexes, 1,2-dimethyllithium naphthene complexes, 3,3-dimethyllithium naphthene complexes, 4,4-dimethyllithium naphthene complexes, and 3,3-4,4-tetramethyllithium naphthene complexes.
[0054] In some specific exemplary embodiments, the solvent of the ether solution mentioned in this invention is selected from at least one of dioxolane, tetrahydrofuran, ethylene glycol dimethyl ether, and 2-methyltetrahydrofuran.
[0055] Optimal selection of the concentration and type of prelithiation solution can make the prelithiation process more gentle and uniform, achieving controllable prelithiation. After prelithiation, the silicon-based anode material has high structural integrity, high initial coulombic efficiency, low interfacial impedance, and better cycle stability.
[0056] In some specific embodiments, the pre-lithiation solution mentioned in this invention can preferably be prepared by the following method: Under an inert atmosphere, a lithium source and an aromatic hydrocarbon ligand are reacted in an ether solvent to obtain a pre-lithiation solution of a lithium complex. The lithium source concentration is 0.5~2.0 mol / L, and the molar ratio of lithium source to aromatic hydrocarbon ligand is 1:0.1~10.
[0057] The degree of pre-lithiation (i.e., the amount of lithium embedded in silicon, characterized by the initial lithium-silicon alloy Li) can be controlled by positively adjusting the lithium concentration in the initial solution and the molar ratio of the lithium source to the aromatic hydrocarbon ligand. x Precise control of the value of x in Si.
[0058] In the preparation of the pre-lithiation solution mentioned in this invention, the ether solvent can be selected from at least one of the above-mentioned dioxolane, tetrahydrofuran, ethylene glycol dimethyl ether and 2-methyltetrahydrofuran.
[0059] In some specific exemplary embodiments, the lithium source concentration in the preparation of the pre-lithiation solution mentioned in this invention can be, for example, a point value or any range of values such as 0.5 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2.0 mol / L.
[0060] In some specific exemplary embodiments, the molar ratio of lithium source to aromatic hydrocarbon ligand in the preparation of the pre-lithiation solution mentioned in this invention can be, for example, a point value or any range of values such as 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10.
[0061] In a specific embodiment, the preparation method of the pre-lithiated anode material mentioned in this invention further includes the following steps: S3. Perform reverse detection on the pre-lithiation silicon-based anode material of S2, and adjust the pre-lithiation processing parameters of S1 according to the reverse detection results to form a closed-loop control of the pre-lithiation degree.
[0062] The method for preparing pre-lithiated anode materials provided by this invention also establishes a "forward regulation-reverse detection" mechanism to achieve precise closed-loop control of the degree of pre-lithiation, ensuring the accuracy of alloy phase composition and compensation of lithium, thereby significantly improving the first coulombic efficiency, cycle life and overall energy density of silicon-based solid-state batteries.
[0063] In some specific exemplary embodiments, the reverse detection mentioned in this invention includes reverse detection of alloy phase composition and actual compensation lithium content.
[0064] In some specific exemplary embodiments, the present invention can determine the active lithium content by titration, such as acid-base titration; determine the Li / Si atomic ratio and chemical state of the surface and bulk phase by X-ray photoelectron spectroscopy (XPS); or detect the alloy phase composition (x value) and actual compensated lithium amount by assembling half-cells and testing open-circuit voltage and initial delithiation capacity. The detection results are fed back to step S1 to form a closed-loop control, ensuring the stability of the pre-lithiation accuracy.
[0065] In a specific embodiment, the present invention also provides a negative electrode sheet, comprising a current collector and an electrode material layer on the surface of the current collector, wherein the electrode material layer uses the pre-lithiated negative electrode material as the active material.
[0066] In some specific exemplary embodiments, the preferred method for preparing the negative electrode sheet mentioned in this invention is as follows: The pre-lithiated negative electrode material, solid electrolyte powder, conductive agent and binder are mixed, and the negative electrode sheet is obtained by dry electrode process or wet electrode process.
[0067] The pre-lithiated anode material of the present invention has good interfacial compatibility and environmental stability with solid electrolytes, significantly improves the air stability of the pre-lithiated material, broadens the electrode processing window, and is compatible with electrode preparation processes under conventional drying chamber environments.
[0068] For example, a dry electrode process can be used.
[0069] The pre-lithiated negative electrode material, solid electrolyte powder, conductive agent and binder are mixed evenly in a dry mixing equipment at a certain mass ratio (e.g., lithium silicon powder: solid electrolyte: conductive agent: binder = 50~90:20~40:5~10:3~8). Then, a continuous electrode film is formed directly on the current collector (e.g., copper foil) by dry calendering or electrostatic spraying without the use of any solvent, thus preparing the negative electrode sheet.
[0070] For example, a wet electrode process can be used.
[0071] The pre-lithiated negative electrode material, solid electrolyte powder, conductive agent and binder are dispersed in an inert solvent that is harmless to the solid electrolyte, stirred to form a uniform slurry, and then coated (e.g., slot coating or doctor blade coating) on the current collector. The slurry is then dried at low temperature (<100°C) under an inert atmosphere to completely remove the solvent, thus obtaining the negative electrode sheet.
[0072] The solid electrolyte powder mentioned in this invention can be selected from one or more of oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, nitride solid electrolytes, and hydride solid electrolytes, preferably Li6PS5Cl and Li 6.4 La3Zr 1.4 Ta 0.6 O 12 .
[0073] The sulfide solid electrolyte is selected from the silver-germanium sulfide type solid electrolyte LiPSMX and the lithium thio-LiSICON type superionic conductor solid electrolyte Li. 4-x A 1-x B xS4 (0<x<1) and one or more of glassy sulfides; wherein M is one or more of O, Cu, Zn, Bi, Sn, Al, Mn, Ce and In, X is one or more of F, Cl, Br and I; A is one or more of Si, Sn, Ge and Zr, B is one or more of O, P, Al, Zn and Ga.
[0074] The oxide solid-state electrolyte is selected from one or more of garnet-type solid-state electrolytes, perovskite-type solid-state electrolytes, NASICON-type solid-state electrolytes and LISICON-type solid-state electrolytes.
[0075] The garnet-type solid-state electrolyte comprises Li x La3Zr y A z O 12 and / or Li x La 3-y B y Zr z O 12 ; wherein A is one or more of Ta, Nb, Mg, Ti, Te, W; B is one or more of Ca, Rb, Al, Ga, and x, y, z are values that satisfy the electroneutrality of the compound.
[0076] The perovskite-type solid-state electrolyte comprises Li 3.3 La 0.53 TiO3, Li 3x La 2 / 3-x TiO3 and at least one of Li x Sr y M z TaO3; wherein M is one or more of Zr and Nb, and x, y, z are values that satisfy the electroneutrality of the compound.
[0077] The NASICON-type solid-state electrolyte comprises Li x Al y M z (PO4)3, Li x Y y Zr z (PO4)3, at least one of LiTi2(PO4)3, LiGe2(PO4)3 and LiGeTi(PO4)3; wherein M is one or more of Ti, Ge, Hf, Zn, Zr and Si, and x, y, z are values that satisfy the electroneutrality of the compound.
[0078] The LISICON-type solid-state electrolyte comprises Li 3+x (P 1-x Si x )O4 and / or Li 3+x Gex V 1-x O₄, where x, y, and z are values that satisfy the electrical neutrality of the compound.
[0079] The halide solid electrolyte is selected from one or more of Li₃OCl, LiI, Li₅ZnI₄, Li₃OCl 1-x Br x (where 0<x<1), Li₂XCl₄ (X is selected from Cd and / or Mg), Li₂X'I₄ (X' is selected from Cd and / or Zn), LiMCl₅X" (M is selected from one or more of La, Ta, Nb, X" is selected from any one of O, Cl, F, OH), Li 3-y ZrᵧM' 1-y Cl₆ (M' is selected from one or more of Y, Er, Yb, Ho, Lu, 0<y<1).
[0080] The binder mentioned in the present invention is selected from one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyethylene oxide (PEO), and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP).
[0081] The conductive agent mentioned in the present invention is selected from one or more of carbon black (Super P), carbon nanotubes, graphene, and carbon fiber (VGCF).
[0082] The inert solvent mentioned in the present invention is selected from one or more of dimethoxyethane (DME), o-xylene, m-xylene, p-xylene, N-methylpyrrolidone, tetrahydrofuran, dimethylformamide, dimethylacetamide, butyrate, toluene, anisole, hexane, heptane, dibromomethane, dichloroethane, ethanol, and glycol ether.
[0083] In specific embodiments, the present invention further provides a battery cell, comprising the negative electrode sheet described above.
[0084] In some specific exemplary embodiments, the present invention further specifically provides a method for preparing a battery cell, comprising: preparing the negative electrode sheet, with reference to the negative electrode sheet protected by the present invention described above.
[0085] preparing the positive electrode sheet, where any one of a dry electrode process and a wet electrode process may be adopted.
[0086] Method A: Dry electrode process.
[0087] The positive electrode active material, solid electrolyte powder, conductive agent, and binder are mixed evenly in a dry mixing equipment at a certain mass ratio (active material: solid electrolyte: conductive agent: binder = 50-90:20-40:5-10:3-8). The mixture is then directly applied to the current collector (such as aluminum foil) by dry calendering or electrostatic spraying without the use of any solvent.
[0088] Method B: Wet electrode process.
[0089] The positive electrode active material, solid electrolyte powder, conductive agent and binder are dispersed in an inert solvent that is harmless to the solid electrolyte, stirred to form a uniform slurry, coated (slit coating or doctor blade coating) on the current collector, and dried at low temperature (<100℃) under inert atmosphere protection to completely remove the solvent, thus obtaining the positive electrode sheet.
[0090] Preparation of solid electrolyte layer: In the presence of a protective gas, solid electrolyte material, binder and solvent are mixed evenly to obtain solid electrolyte slurry. The solid electrolyte slurry is then made into independent sheets and dried to form a solid electrolyte layer.
[0091] Assembly: In an inert atmosphere glove box, the negative electrode, solid electrolyte membrane, and positive electrode are stacked sequentially. A certain pressure (e.g., ≥20 MPa) is applied to press the layers together, ensuring tight contact between the interfaces, thus assembling a solid-state battery (cell).
[0092] The solid electrolyte materials, binders, solvents, and conductive agents mentioned in the preparation of the positive electrode and the solid electrolyte layer can all be selected from the same material sources as those for the negative electrode.
[0093] The positive electrode, negative electrode, and solid electrolyte layer can use the same or different electrolyte materials.
[0094] In the preparation of the positive electrode sheet, the positive electrode active material can be selected from one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, nickel-cobalt-manganese ternary materials, and nickel-cobalt-aluminum ternary materials, preferably LiNi. 0.8 Co 0.1 Mn 0.1 O2 or LiCoO2.
[0095] The pressing mentioned in the assembly steps of this invention can be performed using any of the following methods: roller pressing, hot pressing, or isostatic pressing.
[0096] In a specific embodiment, the present invention also provides a battery cell module, including the negative electrode sheet or the battery cell.
[0097] In a specific embodiment, the present invention also provides a battery pack, including the negative electrode sheet, the battery cell, or the battery cell module.
[0098] In a specific embodiment, the present invention also provides an electrical device, including the negative electrode sheet, the battery cell, the battery cell module, or the battery pack.
[0099] In some specific exemplary embodiments, the electrical devices mentioned in this invention particularly include vehicles.
[0100] Example 1 A pre-lithiated anode material, wherein an oxygen-containing passivation layer is generated in situ on the surface of the lithium-silicon alloy phase particles formed by pre-lithiation, the oxygen-containing passivation layer comprising Li2O, Li2CO3, and SiO x The composite phase has a thickness of 15 nm and a specific surface area of 20 m². 2 / g, lithium-silicon alloy phase particles are Li x Si, x takes the value 1.5.
[0101] This embodiment 1 also specifically provides a method for preparing a pre-lithiated anode material, including the following steps: S1. Under an inert atmosphere, lithium metal (battery grade) and the aromatic hydrocarbon ligand naphthalene were reacted in an ether solvent THF at room temperature to obtain a lithium complex pre-lithiation solution. The lithium source concentration was 1.0 mol / L, and the molar ratio of lithium source to aromatic hydrocarbon ligand was 1:1, resulting in a 1 mol / L naphthalene-lithium complex THF solution. The nano-silicon anode material powder was immersed in the above pre-lithiation solution and stirred at 25°C for 2 hours. The pre-lithiation silicon material was then washed multiple times with hexane and vacuum dried to obtain the pre-lithiation silicon-based anode material. S2. The pre-lithiated silicon-based anode material is placed in an argon atmosphere with an oxygen volume concentration of 1% for surface passivation treatment for 30 minutes to form a surface passivation layer. S3. Reverse polarization analysis was performed on the pre-lithiated silicon-based anode material with surface passivation treatment as described in S2. XPS depth analysis and half-cell testing were conducted on the pre-lithiated silicon-based anode material powder, and the bulk alloying degree was determined to be Li. 1.5 Si, the detected value is fed back to step S1 to adjust the pre-lithiation treatment parameters, forming a closed-loop control of the pre-lithiation degree.
[0102] This embodiment 1 also provides a method for preparing a battery cell, including the following steps: Negative electrode preparation: The pre-lithiated negative electrode material (powder), Li6PS5Cl solid electrolyte powder, VGCF conductive agent and PTFE binder are mixed evenly in a dry mixing equipment at a ratio of 75:20:2:3. The mixture is then formed on a copper foil current collector by dry rolling to obtain the negative electrode. LiNi 0.8 Co 0.1 Mn 0.1O2 positive electrode active material, Li6PS5Cl solid electrolyte powder, VGCF conductive agent and PTFE binder are dry mixed in 75:20:2:3 and rolled onto aluminum foil to obtain positive electrode sheet; Li 6.4 La3Zr 1.4 Ta 0.6 O 12 Solid electrolyte material and binder are mixed with xylene solvent in a 97:3 ratio to form independent sheets, thus obtaining a solid electrolyte layer. The layers are stacked sequentially and subjected to isostatic pressing at 50 MPa to assemble solid-state battery cells.
[0103] Example 2 A battery cell (solid-state) is prepared in a manner that is basically the same as that in Example 1, except that the positive electrode active material is LiCoO2.
[0104] Example 3 A pre-lithiated anode material, wherein an oxygen-containing passivation layer is generated in situ on the surface of the lithium-silicon alloy phase particles formed by pre-lithiation, the oxygen-containing passivation layer comprising Li2O, Li2CO3, and SiO x The composite phase has a thickness of 25 nm and a specific surface area of 2 m². 2 / g, lithium-silicon alloy phase particles are Li x The value of Si and x is 1.4, and the silicon-based material is micron-sized silicon.
[0105] This embodiment 3 also provides a method for preparing a pre-lithiated anode material, which is the same as that in embodiment 1.
[0106] This embodiment 3 also provides a battery cell, which is prepared in the same way as in embodiment 1.
[0107] Example 4 A pre-lithiated anode material, wherein an oxygen-containing passivation layer is generated in situ on the surface of the lithium-silicon alloy phase particles formed by pre-lithiation, the oxygen-containing passivation layer comprising Li2O, Li2CO3, and SiO x The composite phase has a thickness of 25 nm and a specific surface area of 2 m². 2 / g, lithium-silicon alloy phase particles are Li x The value of Si and x is 1.5, and the silicon-based material is a silicon-carbon composite material.
[0108] This embodiment 4 also provides a method for preparing a pre-lithiated anode material, which is the same as that in embodiment 1.
[0109] This embodiment 4 also provides a battery cell, which is prepared in the same way as in embodiment 1.
[0110] Example 5 A pre-lithiated anode material, wherein an oxygen-containing passivation layer is generated in situ on the surface of the lithium-silicon alloy phase particles formed by pre-lithiation, the oxygen-containing passivation layer comprising Li2O, Li2CO3, and SiO x The composite phase has a thickness of 25 nm and a specific surface area of 2 m². 2 / g, lithium-silicon alloy phase particles are Li x The value of Si and x is 1.3, and the silicon-based material is nano-silicon.
[0111] Example 5 also provides a method for preparing a pre-lithiated anode material, which is basically the same as that in Example 1, except that the pre-lithiating agent is a 1 mol / L THF solution of a biphenyl lithium complex.
[0112] This embodiment 5 also provides a battery cell, the preparation method of which is basically the same as that of embodiment 1, the difference being that the solid electrolyte is an oxide Li. 6.4 La3Zr 1.4 Ta0.6O 12 .
[0113] Example 6 A pre-lithiated anode material, wherein an oxygen-containing passivation layer is generated in situ on the surface of the lithium-silicon alloy phase particles formed by pre-lithiation, the oxygen-containing passivation layer comprising Li2O, Li2CO3, and SiO x The composite phase has a thickness of 15 nm and a specific surface area of 20 m². 2 / g, lithium-silicon alloy phase particles are Li x The value of Si and x is 3.2, and the silicon-based material is nano-silicon.
[0114] This embodiment 6 also provides a method for preparing a pre-lithiated anode material, including the following steps: S1. Under an inert atmosphere, lithium metal (battery grade) and the aromatic hydrocarbon ligand naphthalene were reacted in an ether solvent THF at room temperature to obtain a lithium complex pre-lithiation solution. The lithium source concentration was 2.0 mol / L, and the molar ratio of lithium source to aromatic hydrocarbon ligand was 1:1, resulting in a 2 mol / L naphthalene-lithium complex THF solution. The nano-silicon anode material powder was immersed in the above pre-lithiation solution and stirred at 60°C for 4 hours. The pre-lithiation silicon material was then washed multiple times with hexane and vacuum dried to obtain the pre-lithiation silicon-based anode material. S2. The pre-lithiated silicon-based anode material is placed in an argon atmosphere with an oxygen volume concentration of 2% for surface passivation treatment for 45 minutes to form a surface passivation layer. S3. Reverse-bias detection is performed on the pre-lithiated silicon-based anode material that has undergone surface passivation treatment in S2. XPS depth analysis and half-cell testing are conducted on the pre-lithiated silicon-based anode material powder. The detection values are fed back to step S1 to adjust the pre-lithiation treatment parameters. The bulk alloying degree is measured to be Li. 3.2Si forms a closed-loop control of the pre-lithiation degree.
[0115] This embodiment 6 also provides a battery cell, which is prepared in the same way as in embodiment 1.
[0116] Example 7 A pre-lithiated anode material, wherein an oxygen-containing passivation layer is generated in situ on the surface of the lithium-silicon alloy phase particles formed by pre-lithiation, the oxygen-containing passivation layer comprising Li2O, Li2CO3, and SiO x The composite phase has a thickness of 5 nm and a specific surface area of 20 m². 2 / g, lithium-silicon alloy phase particles are Li x The value of Si and x is 2.1, and the silicon-based material is nano-silicon.
[0117] This embodiment 7 also provides a method for preparing a pre-lithiated anode material, including the following steps: S1. Under an inert atmosphere, lithium metal (battery grade) and the aromatic hydrocarbon ligand naphthalene were reacted in an ether solvent THF at room temperature to obtain a lithium complex pre-lithiation solution. The lithium source concentration was 1.0 mol / L, and the molar ratio of lithium source to aromatic hydrocarbon ligand was 1:1, resulting in a 1 mol / L naphthalene-lithium complex THF solution. The nano-silicon anode material powder was immersed in the above pre-lithiation solution and stirred at 40°C for 3 hours. The pre-lithiation silicon material was then washed multiple times with hexane and vacuum dried to obtain the pre-lithiation silicon-based anode material. S2. The pre-lithiated silicon-based anode material is placed in an argon atmosphere with an oxygen volume concentration of 0.1% for surface passivation treatment for 30 minutes to form a surface passivation layer. S3. Reverse-bias detection is performed on the pre-lithiated silicon-based anode material that has undergone surface passivation treatment in S2. XPS depth analysis and half-cell testing are conducted on the pre-lithiated silicon-based anode material powder. The detection values are fed back to step S1 to adjust the pre-lithiation treatment parameters. The bulk alloying degree is measured to be Li. 2.1 Si forms a closed-loop control of the pre-lithiation degree.
[0118] This embodiment 7 also provides a battery cell, which is prepared in the same way as in embodiment 1.
[0119] Example 8 A pre-lithiated anode material, wherein an oxygen-containing passivation layer is generated in situ on the surface of the lithium-silicon alloy phase particles formed by pre-lithiation, the oxygen-containing passivation layer comprising Li2O, Li2CO3, and SiO x The composite phase has a thickness of 30 nm and a specific surface area of 20 m². 2 / g, lithium-silicon alloy phase particles are Li x The value of Si and x is 2.1, and the silicon-based material is nano-silicon.
[0120] This embodiment 8 also provides a method for preparing a pre-lithiated anode material, comprising the following steps: S1. Under an inert atmosphere, lithium metal (battery grade) and the aromatic hydrocarbon ligand naphthalene were reacted in the ether solvent THF at room temperature to obtain a lithium complex pre-lithiation solution. The lithium source concentration was 1.0 mol / L, and the molar ratio of lithium source to aromatic hydrocarbon ligand was 1:1, resulting in a 1 mol / L naphthalene-lithium complex THF solution. The nano-silicon anode material powder was immersed in the above pre-lithiation solution and stirred at 40°C for 3 hours. The pre-lithiation silicon material was then washed multiple times with hexane and vacuum dried to obtain the pre-lithiation silicon-based anode material. S2. The pre-lithiated silicon-based anode material is placed in an argon atmosphere with an oxygen volume concentration of 5% for surface passivation treatment for 30 minutes to form a surface passivation layer. S3. Reverse-bias detection is performed on the pre-lithiated silicon-based anode material that has undergone surface passivation treatment in S2. XPS depth analysis and half-cell testing are conducted on the pre-lithiated silicon-based anode material powder. The detection values are fed back to step S1 to adjust the pre-lithiation treatment parameters. The bulk alloying degree is measured to be Li. 2.1 Si forms a closed-loop control of the pre-lithiation degree.
[0121] This embodiment 8 also provides a battery cell, which is prepared in the same way as in embodiment 1.
[0122] Example 9 A battery cell (solid-state) is prepared in a manner that is basically the same as that in Example 1, except that the thickness of the oxygen-containing passivation layer is 1 nm.
[0123] Example 10 A battery cell (solid-state) is prepared in a manner that is basically the same as that in Example 1, except that the thickness of the oxygen-containing passivation layer is 1 μm.
[0124] Example 11 A battery cell (solid-state) is prepared using a method essentially the same as that in Example 1, except that the specific surface area of the oxygen-containing passivation layer is 0.1 m². 2 / g.
[0125] Example 12 A battery cell (solid-state) is prepared using a method essentially the same as that in Example 1, except that the oxygen-containing passivation layer has a specific surface area of 200 m². 2 / g.
[0126] Comparative Example 1 A battery cell, the manufacturing method of which is as follows: Negative electrode preparation: Nano-silicon powder, Li6PS5Cl solid electrolyte powder, VGCF conductive agent and PTFE binder are mixed evenly in a dry mixing equipment at a ratio of 75:20:2:3. A continuous electrode film is formed on a copper foil current collector by dry rolling to obtain the negative electrode. LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode active material, Li6PS5Cl solid electrolyte powder, VGCF conductive agent and PTFE binder are dry mixed in 75:20:2:3 and rolled onto aluminum foil to obtain positive electrode sheet; Li 6.4 La3Zr 1.4 Ta 0.6 O 12 Solid electrolyte material and binder are mixed with xylene solvent in a 97:3 ratio to form independent sheets, thus obtaining a solid electrolyte layer. The layers are stacked sequentially and subjected to isostatic pressing at 50 MPa to assemble solid-state battery cells.
[0127] Comparative Example 1 did not undergo pre-lithiation treatment of the negative electrode material.
[0128] Comparative Example 2 A pre-lithiated anode material is prepared in a manner basically the same as in Example 1, except that it is not subjected to S2 low-oxygen atmosphere passivation treatment.
[0129] The entire process of dry electrode preparation and battery assembly was carried out directly in a strictly controlled argon glove box (O2 < 0.1 ppm, H2O < 0.1 ppm). The composition of the negative electrode, positive electrode, and solid electrolyte was the same as in Example 1.
[0130] Performance testing The performance of the battery cells using the pre-lithiated anode materials in the above embodiments and comparative examples was tested, and the specific testing methods are as follows: Reverse detection of alloy phases (x-value) was performed according to XPS determination, in accordance with YS / T1613.1-2023 General Rules for X-ray Photoelectron Spectroscopy of Surface Chemical Analysis. Test: Sample was transferred under argon protection, and Li 1s and Si 2p peaks were measured by XPS. The surface Li / Si atomic ratio was quantified, and x-values were calculated.
[0131] Initial coulombic efficiency (%) determination: The cell was placed in a 35℃ oven and left to stand for 12 hours. It was then charged at 0.1C to the upper limit voltage, converted to CV to 0.05C, left to stand for 1 hour, and discharged at 0.1C to the lower limit voltage. The discharge capacity was recorded as C0, and the cell was left to stand for 1 hour. The initial coulombic efficiency ICE is the ratio of the initial discharge capacity to the initial charge capacity.
[0132] The method for determining the capacity retention rate (%) after 100 cycles of normal assembly is as follows: Under 35℃ conditions, test the cycle life according to the following steps: a) Discharge at 1C to the termination voltage; b) Let stand for 30 minutes; c) Charge the battery at a constant current of 1C until the individual cells reach the termination voltage, then switch to constant voltage charging and stop charging when the charging current drops to 0.05C. d) Let stand for 30 minutes; e) Discharge at 1C until the discharge termination voltage, and record the discharge capacity; f) Repeat steps b) to e) 100 times consecutively to measure the discharge capacity.
[0133] The initial efficiency (%) of the assembled pre-lithiated anode was simulated after 24 hours of air exposure in a drying chamber, reflecting the stability of the pre-lithiated layer after 24 hours of exposure in a drying chamber (low dew point). The test procedure is as follows: Sample preparation: Pre-lithiated negative electrode sheets from the same batch were divided into two groups: Control group: Direct assembly in a normal dry room (dew point ≤ -40℃) (same as normal assembly first effect).
[0134] Exposure group: placed in a dry room (temperature 25℃, dew point -40℃) and exposed for 24 hours (laid flat, with one side exposed to air).
[0135] Assembly: After exposure of the electrode, the cell is assembled under the same conditions (same as the control group).
[0136] First-time performance test: The charge and discharge procedure is exactly the same as that of a normal assembly for first-time performance.
[0137] Calculation: Using the same first-effect formula, compare the first-effect difference between the exposed group and the control group to assess the stability of pre-lithiation.
[0138] The specific test results are shown in Table 1.
[0139] Table 1. Cell performance test results of the examples and comparative examples
[0140] The data in Table 1 shows that, by comparing Example 1 and Example 6, the combination of the "forward regulation-reverse detection" mechanism allows for the detection feedback adjustment of the pre-lithiation step. By changing the initial concentration, temperature, and time (forward regulation), reverse detection confirms that the x-value is precisely increased from 1.5 to 3.2, and the first coulombic efficiency is also increased from 99.25% to 99.62%, demonstrating the effectiveness of closed-loop control and significantly improving the first coulombic efficiency of the silicon anode.
[0141] The data in Table 1 also shows that the retention rate of Example 1 after 100 cycles was 98.24%, while that of Comparative Example 2, which also underwent pre-lithiation but without a passivation layer, was only 82.30%. This demonstrates that the present invention effectively blocks highly active Li₂ through a low-oxygen passivation layer. x The continuous side reactions between Si and the sulfide electrolyte significantly improve interfacial stability.
[0142] Similarly, in a simulated actual production drying chamber environment (exposed for 12 hours), the first efficiency of Example 1 was still as high as 96.15%, while the first efficiency of Comparative Example 2 (without passivation) was reduced to 45.20%. This proves that the passivation layer formed by the low-oxygen surface oxidation of the present invention greatly improves the air stability of the material, broadens the processing window, and makes it feasible for industrial production.
[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A pre-lithiated anode material, characterized in that, It is composed of silicon particles with a core-shell structure, wherein the core is a silicon matrix phase and the shell is a lithium silicon alloy phase, and the outer layer of the lithium silicon alloy phase is covered with an oxygen-containing passivation layer. The oxygen-containing passivation layer is a composite phase comprising Li₂O, Li₂CO₃, and SiO₂, with a thickness of 1 nm to 1 μm and a specific surface area of 0.1 to 200 m². 2 / g.
2. The pre-lithiated anode material according to claim 1, characterized in that, The thickness of the oxygen-containing passivation layer is 5~30nm, preferably 5~25nm.
3. The pre-lithiated anode material according to claim 1 or 2, characterized in that, The specific surface area of the oxygen-containing passivation layer is 2~20m². 2 / g.
4. The pre-lithiated anode material according to any one of claims 1 to 3, characterized in that, The lithium-silicon alloy phase is Li x The values of Si and x are 1.5 to 3.5, preferably 2 to 3.
2.
5. A method for preparing the pre-lithiated anode material according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1. The silicon-based anode material powder is immersed in a pre-lithiation solution to carry out a pre-lithiation reaction at a reaction temperature of 20~60℃ and a reaction time of 0.5~4h to obtain a pre-lithiation silicon-based anode material; S2. The pre-lithiated silicon-based anode material is placed in an atmosphere with an oxygen volume concentration of 0.1-5% for surface passivation treatment to obtain the pre-lithiated silicon-based anode material. The treatment time is 10-20 min.
6. The method for preparing the pre-lithiated anode material according to claim 5, characterized in that, The pre-lithiation solution is an ether solution of a 1-2 mol / L lithium complex; Preferably, the lithium complex is selected from one or more of lithium biphenylene complex and lithium naphthylene complex; Preferably, the solvent of the ether solution is selected from at least one of dioxolane, tetrahydrofuran, ethylene glycol dimethyl ether, and 2-methyltetrahydrofuran.
7. The method for preparing the pre-lithiated anode material according to claim 6, characterized in that, The pre-lithiation solution is prepared by the following method: Under an inert atmosphere, a lithium source and an aromatic hydrocarbon ligand are reacted in an ether solvent to obtain a pre-lithiation solution of a lithium complex. The lithium source concentration is 0.5~2.0 mol / L, and the molar ratio of lithium source to aromatic hydrocarbon ligand is 1:0.1~10.
8. The method for preparing the pre-lithiated anode material according to any one of claims 5 to 7, characterized in that, It also includes the following steps: S3. Perform reverse testing on the pre-lithiation silicon-based anode material of S2, and adjust the pre-lithiation processing parameters of S1 based on the reverse testing results to form a closed-loop control of the pre-lithiation degree. Preferably, the reverse detection includes reverse detection of alloy phase composition and actual compensation lithium content; Preferably, the detection method for the reverse detection is selected from any one of acid-base titration, XPS depth analysis, or half-cell testing.
9. A negative electrode sheet, comprising a current collector and an electrode material layer on the surface of the current collector, characterized in that, The electrode material layer uses the pre-lithiated negative electrode material as described in any one of claims 1 to 4 as the active material.
10. The negative electrode sheet according to claim 9, characterized in that, The method for preparing the negative electrode sheet is as follows: The pre-lithiated anode material, solid electrolyte powder, conductive agent and binder are mixed, and the anode sheet is obtained by dry electrode process or wet electrode process. Preferably, the solid electrolyte powder is selected from one or more of oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, nitride solid electrolytes, and hydride solid electrolytes; The preferred mass ratio of the pre-lithiated anode material, solid electrolyte powder, conductive agent and binder is 50~90:20~40:5~10:3~8.
11. A battery cell, characterized in that, Includes the negative electrode sheet as described in claim 9 or 10.
12. A battery cell module, characterized in that, It includes the negative electrode sheet as described in claim 9 or 10 or the battery cell as described in claim 11.
13. A battery pack, characterized in that, It includes the negative electrode sheet of claim 9 or 10, the battery cell of claim 11, or the battery cell module of claim 12.
14. An electrical appliance, characterized in that, It includes the negative electrode sheet of claim 9 or 10, the cell of claim 11, the cell module of claim 12, or the battery pack of claim 13.
15. The electrical appliance according to claim 14, characterized in that, The electrical equipment includes vehicles.